The complexity of European Border Control System and Illegal Migration Issue - Emilia JANKOWSKA-AMBROZIAK; Arkadiusz NIEDZWIECKI; Marek PRONIEWSKI (Communications of International Proceedings, 2024)
The evolving role of the European borders necessitates policy revisions due to escalating security costs and the imperative for effective management. Physical barriers built by nations alone are insufficient for border security, as evidenced by European practices. On the other hand, the European Union allocates billions of dollars to border security itself, with Frontex, the EU’s border agency, receiving a substantial portion of the border security budget. The budget has increased by over 150 times in the past two decades, primarily driven by migration crises and the COVID-19 pandemic. Despite the EU funding, member states have independently implemented border security measures, including temporary closures, additional security services, and the construction of fences and walls. While some countries have constructed walls, illegal border crossings have persisted, indicating the uncertainty surrounding their effectiveness. The primary challenge lies in the lack of adequate cooperation conditions between EU border institutions and EU countries. This impedes effective collaboration and results in higher costs. Furthermore, the diverse migration policies adopted by countries exacerbate the complexity of the problem. The paper aims to present the complexity of border security system in the EU, both its central and national part, and its impact on illegal migration flows, as well as to identify the most pressing issues that necessitate revision.
Keywords: Frontex; migration; border; fences